Diversity of trends in occupational injury mortality in the United States, 1980–96. Issue 1 (1st March 2003) - Loomis, D; Bena, J F; Bailer, A J
Abstract : Objectives: Although the United States has generally enjoyed declining rates of fatal occupational injury, the rate of decline has not been uniform. To examine the heterogeneity of trends, changes in fatal occupational injury rates from 1980 to 1996 were estimated by occupation, industry, geographic region, and demographic group. Methods: Deaths due to injury at work during 1980–96 were identified from the US National Traumatic Occupational Fatality database and populations at risk were estimated from the census of population. Mortality rates were computed for unintentional injuries, homicides, and all injuries combined. The annual rate of change was estimated using Poisson regression to model the death rate as a function of time. Results: The estimated average rates for all fatal occupational injuries and for unintentional injuries declined by 3% per year, while the estimated rate of homicide declined <1% per year. The improvement was faster for men (3% per year) than for women (<1% per year) and for younger relative to older workers (7% per year v 2%–3% per year). Trends were also geographically heterogeneous, with the most rapid declines (7%–8% per year) in the South and West. Injury rates for most occupations and industries declined at near the average rate, but some experienced no change or an increase. The rate of homicide also increased in a number of occupations and industries. Conclusions: Broad downward trends in occupational fatality rates may be explained by several factors, including organized safety efforts, product and process changes, and the ongoing shift of employment toward safer sectors. Disparities in fatal injury trends draw attention to potential opportunities to reduce risk: work settings with increasing injury rates are of particular concern.